Creativity measured by divergent thinking is associated with two axes of autistic characteristics - Takeuchi, Hikaru; Taki, Yasuyuki; Sekiguchi, Atsushi; Nouchi, Rui; Kotozaki, Yuka; Nakagawa, Seishu; Miyauchi, Carlos M.; Iizuka, Kunio; Yokoyama, Ryoichi; Shinada, Takamitsu; Yamamoto, Yuki; Hanawa, Sugiko; et al. (Frontiers in Psychology, 2014)
Creativity generally involves the conception of original and valuable ideas, and it plays a key role in scientific achievement. Moreover, individuals with autistic spectrum conditions (ASCs) tend to achieve in scientific fields. Recently, it has been proposed that low empathizing and high systemizing characterize individuals with ASCs. Empathizing is the drive to identify the mental status of other individuals and respond to it with an appropriate emotion; systemizing is the drive to analyze a system. It has been proposed that this higher systemizing underlies the scientific achievement of individuals with ASCs, suggesting the possible positive association between creativity and systemizing. However, previous findings on the association between ASCs and creativity were conflicting. Conversely, previous studies have suggested an association between prosocial traits and creativity, indicating the possible association between empathizing and creativity. Here we investigated the association between creativity measured by divergent thinking (CDT) and empathizing, systemizing, and the discrepancy between systemizing and empathizing, which is called D score. CDT was measured using the S-A creativity test. The individual degree of empathizing (empathizing quotient, EQ) and that of systemizing (systemizing quotient, SQ), and D score was measured via a validated questionnaire (SQ and EQ questionnaires). The results showed that higher CDT was significantly and positively correlated with both the score of EQ and the score of SQ but not with D score. These results suggest that CDT is positively associated with one of the characteristics of ASCs (analytical aspects), while exhibiting a negative association with another (lower social aspects). Therefore, the discrepancy between systemizing and empathizing, which is strongly associated with autistic tendency, was not associated with CDT.